Pembelajaran Pendidikan Agama Islam bagi Anak Tunalaras di SLB E Prayuwana Yogyakarta - Cica Wiswanti; Difa Ul Husna (Equilibrium: Jurnal Pendidikan, 2021)
Education has a function including making people fear God Almighty and build noble morals. Education is a right for anyone, not least for children with special needs with disabilities, including religious education. Islamic Religious Education is education that instills faith and religious values as well as good moral learning. This study intends to provide a description or description of the implementation of Islamic Religious Education learning for children with Tunalaras at SLB E Prayuwana Yogyakarta. The method we use is descriptive research method with data collection techniques through observation and interviews with a number of related parties. The analysis technique used in this study is a qualitative analysis technique in which the research data will be analyzed in a narrative. As a result, Islamic Religious Education for children with disabilities at SLB E Prayuwana Yogyakarta is carried out like a school in general and what distinguishes it is only in terms of teaching methods. In addition, at SLB E Prayuwana Yogyakarta, students emphasize more on learning Al-Quran. This is done with the hope that children with disabilities there will be able to benefit from reading the Al-Quran.